Tafsir Ayat-ayat Al-Qur'an Tentang Landasan Pendidikan Islam - Elga Febriani; Faruh Lestari; Suciati Suciati; Agus Rifki Ridwan (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Humans, as creations of Allah SWT, are entrusted with the mandate to prosper the earth; therefore, divine revelations were sent down, culminating in the Qur’an as the ultimate guide for life. Islam, as a universal religion, emphasizes education as a means to achieve a complete and meaningful life. Islamic education, as defined by scholars such as al-Syaebani, Zakiah Drajat, and Muhaimin, is a process of transforming human behavior in personal, social, and environmental contexts based on Islamic values. This study employs a library research method with a thematic tafsir (maudhu’i) approach to examine the Qur’anic foundations of Islamic education. The findings indicate that verses such as QS. Al-‘Alaq [96]:1–5 highlight the importance of literacy as the starting point of education, QS. Al-Mujadalah [58]:11 affirms the elevated status of the learned, QS. An-Nahl [16]:78 emphasizes human innate potential, QS. Luqman [31]:12–19 stresses character education, and QS. Ali Imran [3]:190–191 underscores the integration of spirituality and intellect. Thus, the Qur’anic foundation provides theological, philosophical, and practical bases for the development of Islamic education aimed at forming insan kamil—individuals who are knowledgeable, faithful, and morally upright. QS. Luqman: 13–19 highlights education based on monotheism and morals, where Luqman advises his children to have faith, do good deeds and be patient. QS. Al-Māidah: 67 emphasizes trust and courage in conveying knowledge, as Allah commanded the Prophet to convey revelation without fear